The Impact of Tourism Attraction Revitalization on the Economy of the Local Community of Lubang Jepang Gunung Pangilun Padang - Hafiz Al Haqqi; Adek Kurnia Fiza (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
This study examines the impact of revitalizing the Lubang Jepang tourist attraction in Gunung Pangilun, Padang City, on the local community's economy. The background of this research is the importance of tourism development as an effort to improve the welfare of the surrounding community. The aim of this research is to analyze the extent to which the revitalization contributes to increasing local community income, business opportunities, and overall economic development. The research method used is descriptive qualitative, with data collected through surveys and interviews with stakeholders, the local community, and business actors in the tourism sector. The results show that the revitalization of the Lubang Jepang tourist attraction has a positive impact on the local economy, as evidenced by increased community income and the emergence of business opportunities, especially initially. However, the sustainability of this positive impact is highly dependent on adequate infrastructure support, the expansion of the tourist area, and effective promotion. The implications of these findings indicate that sustainable management and active community participation are crucial to ensuring that the positive impact can continue and develop.